Flavan-3-ol Isomers Isolated from Euphorbia Thymifolia Linn - Kainsa, Sushma; Singh, Randhir (Pharmacognosy Communications)
Objective: Isolation and identification of phytoconstituents from methanolic extract of whole herb of Euphorbia thymifolia L. Material and Methods: Methanolic extract of Euphorbia thymifolia whole herb was prepared by hot soxhalation method and Flavan-3-ol isomers (compound (I) and (II)) were isolated using chromatographic techniques. The structural identification Flavan-3-ol was carried out by employing Infra red spectroscopy (IR) and 1H Nuclear magnetic Resonance technique. Spectral data obtained was compared with the available literature. Results and conclusion: Spectral analysis revealed compound (I) and (II) as catechin and epicatechin respec- tively. These compounds have been reported for the first time in this plant and can serve as a useful tool in its standardization.
Keywords: Euphorbia thymifolia; Flavan-3-ol; Catechin; Epicatechin etc